Ecopoetry: Overcoming Anthropocene melancholia in the work of Juliana Spahr and Allison Cobb - Marques, Nuno (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2023)
Traditionally, elegy moves from loss to consolation by framing death within larger regenerative cycles of nature. But in the current time of ecological disruption, nature as regeneration is no longer available, and this absence hinders the process of mourning, not allowing consolation. In parallel, the large scale of the environmental crisis creates a sense of futility of action. Both the inability to overcome mourning and the lack of will to act for environmental change create a permanent state of grief that Juliana Spahr, Joshua Clover and Allison Cobb term West Melancholia. How can ecopoetry overcome the process of mourning for lost ecosystems and species, and instead contribute to action? I propose that in contemporary North-American ecopoetry, consolation is given by poetic research in language and activist engagement. Spahr’s "Gentle Now, Don’t Add to Heartache" (2011) and Misanthropocene: 24 Theses (2014), co-authored with Clover, tie grief to the failure of inherited models of representing nature and instead suggest consolation in ecopoetry as activist practice. Cobb’s After We All Died (2016) grounds consolation in a practice of starting from failure to researching language for modes of overcoming grief. I discuss these works to uncover the poets’ proposals of overcoming melancholia through exploration of language and engaged activist writing.